Information Technology Governance Using the COBIT 2019 Framework at PT Bank Pembangunan Daerah Papua - Lompoliu, Erienika; William Tangka, George Morris (Malikussaleh University, Aceh, Indonesia, 2024)
Effective and efficient information technology (IT) management is crucial for the banking industry, especially for PT Bank Pembangunan Daerah Papua (BPDP), which seeks to reinforce its role within the Papua region. Leveraging the COBIT 2019 framework, BPDP aims to enhance IT governance, addressing operational efficiency, information security, and regulatory compliance. This study highlights BPDP's strategic priorities, such as revenue growth, fostering innovation, and customer service excellence, which are essential for sustaining competitive advantage amidst regional geopolitical challenges. By identifying these key priorities, the research uncovers critical areas of improvement, including IT investment optimization, mitigation of regulatory and security risks, and solidifying IT's strategic role in driving business growth. To evaluate BPDP's IT governance maturity, this study applies COBIT 2019's ten design factors, from enterprise goals and risk profiles to IT-related issues, compliance needs, and technology adoption strategies. The findings underscore gaps in risk management, project lifecycle oversight, and resource allocation, offering actionable insights for governance improvement. Enhanced IT integration can support BPDP's larger objectives of sustainable growth and economic development within the region. Furthermore, the study demonstrates that a well-structured governance framework strengthens BPDP's operational efficiency, builds customer trust, and ensures alignment with regulatory standards and evolving technology landscapes. By adopting these governance recommendations, BPDP can achieve long-term success and secure its position as a prominent financial institution in Papua, thus reinforcing its commitment to regional economic growth and compliance with national regulatory standards.